Respostas

2014-06-29T18:39:14-03:00
1) Resolva as equações biquadradas
 
A- 4x(á quarta) - 37x² + 9 = 0

4x⁴ - 37x² + 9 = 0     para   y = x²
y²   - 37y + 9 = 0
a = 1
b = -37
c = 9
Δ = b² - 4ac
Δ = (-37)² - 4(4)(9)
Δ = 1369 - 144
Δ = 1225-----------------------------√1225 = 35
se

Δ > 0 
então (baskara)

y = - b - + √Δ/2a
y' = -(-37) - √1225/2(4)
y' = + 37 - 35/8
y' = 2/8
y' = 1/4

y" = -(-37) + √1225/2(4)
y" = + 37 + 35/8
y" = 72/8
y" = 9

se
 y = x²
x² = y     ------------paea y = 1/4 e 9
x² = 1/4
x = - + √1/4
          1        √1         1
x = √----  =  ------- =   -----
         4        √4           2

x' = - 1/2
x" = + 1/2

x² = y  para   y = 9
x² = 9
x= - + √9
x₃ = - 3
x₄ = + 3

então

x₁ = -1/2
x₂ = + 1/2
x₃ = - 3
x₄ = + 4


B- 11x(á quarta) - 7x² - 4 = 0

11x⁴ - 7x² - 4 = 0      para   y = x²
11y² - 7y  - 4 = 0
a = 11
b = - 7
c = - 4
Δ = b² - 4ac
Δ = (-7)² - 4(11)(-4)
Δ = 49 + 176
Δ = 225----------------------------------√225 = 15
se
Δ > 0
então(baskara)

y = - b - + √Δ/2a

y₁ = -(-7) - √225/2(11)
y₁ = + 7 - 15/22
y₁ = -8/22
y₁ = - 4/11

y₂ = -(-7) +  √225/2(11)
y₂ = + 7 + 15/22
y₂ = 22/22
y₂ = 1

se

y = x²
x² = y   para y₁ = -4/11
x² = -4/11
x =  √ -4/11   Não tem ZEROS  reais   Ф

para y₂ = 1

y = x²
x² = y
x² = 1
x = - + √1
x = - 1
x = +1

assim

x₁ = Ф
x₂ = Ф
x₃ = - 1
x₄ = + 1




C- x(á quarta) - 41x² + 400 = 0 

  x
⁴ - 41x² + 400 = 0   para    y = x²
  y² - 41x  + 400 = 0
a = 1
b = - 41
c = 400
Δ =b² - 4ac
Δ = (-41) - 4(1)(400)
Δ = 1681 - 1600
Δ = 81 ---------------------------------------√81 = 9
se
Δ > 0
então(baskara)

y = - b - = √Δ/2a

y₁ = -(-41) - √81/2(1)
y₁= + 41 - 9/2
y₁ = 32/2
y₁ = 16

y₂= -(-41) + √81/2(1)
y₂ = + 41 + 9/2
y₂= 50/2
y₂ = 25

para y = x²
x² = y   -----------------para y₁  16 e y₂= 25
x² = 16
x = - + √16
x = - 4
x = + 4

x² = y
x² = 25
x = - +√√ 25
x = - 5
x = + 5

então
x₁ = - 4
x₂ = + 4
x₃ = - 5
x₄ = + 5